2010
DOI: 10.1086/656588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Characteristics of Patients with 2009 Pandemic Influenza A (H1N1) Virus Infection after Vaccination

Abstract: Although the clinical consequences of infection are comparable between vaccinated and unvaccinated patients, humoral and cellular immune responses in vaccinated patients are boosted for some weeks, indicating an additional benefit of vaccination against 2009 pandemic influenza A (H1N1) virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Seroprotection rates following seasonal influenza vaccination do not tend to drop substantially from their peak, within 3 months of vaccination [44], [45]. Another study found that geometric mean titers could remain above seroprotective levels within 3 months of pH1N1 vaccination for adults aged between 18 and 28 [46]. Therefore a delay or decline in antibody response following receipt of pH1N1 vaccine is unlikely to explain our findings.…”
Section: Discussionmentioning
confidence: 55%
“…Seroprotection rates following seasonal influenza vaccination do not tend to drop substantially from their peak, within 3 months of vaccination [44], [45]. Another study found that geometric mean titers could remain above seroprotective levels within 3 months of pH1N1 vaccination for adults aged between 18 and 28 [46]. Therefore a delay or decline in antibody response following receipt of pH1N1 vaccine is unlikely to explain our findings.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to local infection, live virus can also disseminate systemically and can be found in the gut or in the blood (43,44). In a recent study, similar peak levels of MN titer were found in patients with pandemic 2009 H1N1 infection or vaccine recipients (23). However, the sample size was small, and only military personnel aged between 18 and 28 were recruited in the study.…”
Section: Discussionmentioning
confidence: 97%
“…Sensitivity was 100% for the specimens with influenza A copy numbers of greater than or equal to 10 5 copies/ml and was 96% for specimens with copy numbers greater than or equal to 10 3 copies/ml. Typical viral loads in the nasopharynx for patients recently infected with influenza A are rarely below 10 4 copies/ml [41], [42], and this has been verified for several strains [43]. So, while there are several ways that the reported microfluidic assay could be improved to lower the limit of detection, in the case of influenza A infections, this improvement would be of limited benefit.…”
Section: Discussionmentioning
confidence: 99%